2013
DOI: 10.3389/fpls.2013.00270
|View full text |Cite
|
Sign up to set email alerts
|

Effects of foliar boron application on seed composition, cell wall boron, and seed δ15N and δ13C isotopes in water-stressed soybean plants

Abstract: Limited information is available on the effects of foliar boron (B) application on soybean seed composition. The objective of this research was to investigate the effects of foliar B on seed composition (protein, oil, fatty acids, and sugars). Our hypothesis was that since B is involved in nitrogen and carbon metabolism, it may impact seed composition. A repeated greenhouse experiment was conducted where half of the soybean plants was exposed to water stress (WS) and the other half was well-watered. Foliar bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 99 publications
(140 reference statements)
4
47
0
1
Order By: Relevance
“…Dordas & Brown (2001) and Stangoulis et al (2001), support this, since boron can cross membranes via passive absorption to reach boron requirements for plant. Dannel et al (2002), Dordas et al (2000) and Bellaloui et al (2013) observed that in squash roots, diffusing across plasma-membrane vesicles was slightly depressed by mercuric chloride, similar finding were reported by Trivedi (2015).…”
Section: Uptake Of Boron By Plantssupporting
confidence: 84%
See 2 more Smart Citations
“…Dordas & Brown (2001) and Stangoulis et al (2001), support this, since boron can cross membranes via passive absorption to reach boron requirements for plant. Dannel et al (2002), Dordas et al (2000) and Bellaloui et al (2013) observed that in squash roots, diffusing across plasma-membrane vesicles was slightly depressed by mercuric chloride, similar finding were reported by Trivedi (2015).…”
Section: Uptake Of Boron By Plantssupporting
confidence: 84%
“…Trivedi (2015), Planchet et al (2011) and Bellaloui et al (2013) reported that the formation of esters borate through the interaction with hydroxyl groups of cell wall has been advanced as a mechanism for interacting with cell wall polymers. Casassa et al (1986) and Sarquis (1986) explained this phenomenon and sliding properties of "slime".…”
Section: Uptake Of Boron By Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bellaloui and Turley (2013), observed the relationship among protein and oil contents under greenhouse conditions, and found that fuzzless cotton seeds accumulated higher oil and lower protein content compared with their equivalent fuzzy seeds, showing an inverse relationship between protein and oil contents. The inverse relationship between amount of protein and oil was previously reported in other species such as corn (Kebede et al, 2013), soybean (Burton, 1985;Ray et al, 2006;Bellaloui et al, 2013aBellaloui et al, , 2013b, and cottonseed (Pettigrew & Dowd, 2011). Only a few studies have attempted to discuss variability in cottonseed fatty acid profiles, the source of the variation, or how fatty acid percentages correlate with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Soybean plants with the application of 5 ppm B increased weight 100 grain 6.41% higher than those without B ( Table 2). The research of Bellaloui et al (2013) indicated that the application of B through the leaves could increase the seed weight (100 grain weight) of 16.1 g higher than those without B of 13.2 g of soybean on treatment given water. This is in line with Rio Tinto (2012) stated that the addition of boron in plants could increase the success of flower pollination and had a role in seed formation, and application of boron on soybean plant increased the weight of 100 grain.…”
Section: -Grain Weight (G)mentioning
confidence: 99%